Academic dishonesty among health sciences postgraduate students: a single center cross-sectional analysis / Siti Shahara Zulfakar … [et al.] - Zulfakar, Siti Shahara; Mat Ludin,, Arimi Fitri; Othman, Mohd. Sham; Che Wan Mohd Rozali,, Wan Nor Atikah; Tahir, Ahmad Rashidi; Nordin, Naufal; Mohamad Sulaiman, Nur Nabilah; Shamsudin, Syazawani; Che Razali, Nur Syahirah; Haezam, Farah Natasha; Buang, Nurul Fairuz (Universiti Teknologi MARA, Perlis, 2023)
Academic dishonesty/misconduct has been one of the major issues in Malaysia which is widespread in the higher learning institutions. It implies any type of fraudulent act among students such as paying another person to do the task, purchasing a class research paper, getting test questions before the date of an examination, or duplicating the finished work of another student that applies to formal academic exercises. This cross-sectional study was conducted to determine the practice of academic dishonesty among postgraduate students in the Faculty of Health Sciences, UKM KL. The McCabe Academic Integrity Questionnaire was adopted and distributed to the respondents. Results show that there is a low frequency of academic dishonesty involved among research and coursework postgraduate students and there are no significant differences between both modes of the study. Age and gender show a significant correlation with academic dishonesty practices among all four demographic factors studied.